2016
DOI: 10.1089/neu.2015.4207
|View full text |Cite
|
Sign up to set email alerts
|

Early Decompression following Cervical Spinal Cord Injury: Examining the Process of Care from Accident Scene to Surgery

Abstract: Early decompression may improve neurological outcome after spinal cord injury (SCI), but is often difficult to achieve because of logistical issues. The aims of this study were to 1) determine the time to decompression in cases of isolated cervical SCI in Australia and New Zealand and 2) determine where substantial delays occur as patients move from the accident scene to surgery. Data were extracted from medical records of patients aged 15-70 years with C3-T1 traumatic SCI between 2010 and 2013. A total of 192… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 34 publications
(37 reference statements)
3
36
0
Order By: Relevance
“…Early Decompression following Cervical Spinal Cord Injury: Examining the Process of Care from Accident Scene to Surgery published by the Journal of Neurotrauma in 2015 collected the data of 192 patients across Australasia between 2010 and 2013. The aims were to determine the time to decompression in cases of isolated cervical spinal injury and areas of delay from accident scene to surgery with 12 patients in the Auckland region . This audit aims to continue a follow up study to re‐examine the post injury process; and forms a comparison between the patients from 2010 to 2013 to the group after the implementation of the New Zealand Spinal Cord Impairment Action Plan.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…Early Decompression following Cervical Spinal Cord Injury: Examining the Process of Care from Accident Scene to Surgery published by the Journal of Neurotrauma in 2015 collected the data of 192 patients across Australasia between 2010 and 2013. The aims were to determine the time to decompression in cases of isolated cervical spinal injury and areas of delay from accident scene to surgery with 12 patients in the Auckland region . This audit aims to continue a follow up study to re‐examine the post injury process; and forms a comparison between the patients from 2010 to 2013 to the group after the implementation of the New Zealand Spinal Cord Impairment Action Plan.…”
Section: Introductionsupporting
confidence: 91%
“…Comparisons were made between the groups before and after the New Zealand Spinal Cord Impairment Action Plan. A previous study analysing the New Zealand demographic showed patients who were admitted directly to a specialist tertiary unit had significantly reduced time to decompression than those admitted first to an initial regional hospital . Our results were consistent with this.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations